Phosphorothioated and phosphate-terminal dumbbell (PP-TD) probe-based rapid detection of polynucleotide kinase activity. Issue 22 (10th October 2022) - Jiang, Xianfeng; Shen, Xudan; Talap, Jadera; Yang, Dan; Zeng, Su; Liu, Hui; Cai, Sheng
Abstract : A primer-free, sensitive assay has been developed to detect polynucleotide kinase (PNK) activity. This proposed method provides a promising platform for PNK activity monitoring and inhibition screening for drug discovery and clinical treatment. Abstract : Polynucleotide kinase (PNK), a bifunctional enzyme with 5′-kinase and 3′-phosphatase activities, plays an important role in DNA repair and is associated with various diseases. Here, we developed a primer-free, sensitive, and isothermal quantitative assay to detect PNK activity. In the presence of PNK, the 3′-phosphate group of the substrate was digested with 3′-OH, initiating the amplification reaction. Elongated dsDNA binds to the dsDNA-specific fluorescent dye EvaGreen, leading to a significant enhancement in fluorescence intensity. The limit of detection (LOD) of this method was 7.7 × 10 −7 U μL −1, which is comparable or even superior to that of previously reported methods. This approach also showed good quantitative ability in complex cell lysates, indicating potential for biological sample analysis. Additionally, this facile and sensitive assay can be used to screen for PNK inhibitors. The proposed method provides a promising platform for sensitive PNK activity monitoring and inhibition screening for drug discovery and clinical treatment.